Paragonimus and paragonimiasis in northern Peru. Natural infection in Pseudothelphusa chilensis by metacercariae of Paragonimus Braun, 1899 - Cuba, César (1974)
The index of natural infection and the density of parasitism in crabs collected in three provinces of the Department of Cajamarca, Peru, have been studied, and they have revealed that metacercariae of Paragonimus Braun, 1899 are found in 43.97% of 539 specimens of Pseudothelphusa chilensis Milne Edwards, 1843, the unique crab found in the zone. The parasited organ was almost exclusively the hepatopancreas averaging 10.33 metacercarias per crab. The adult specimens which were inoculated with metacercariae were identified as Paragonimus peruvianus Miyazaki, Ibáñez & Miranda, 1969, with the exception of three samples which belonging to the species Paragonimus caliensis Little, 1968.